Sibling Spillovers and Free Schooling - Jo\~ao R. Ferreira; Wayne Aaron Sandholtz (CESifo GmbH, 2024)
We use administrative data to measure sibling spillovers on academic performance before and after Tanzania's introduction of Free Secondary Education (FSE). Prior to FSE, students whose older siblings narrowly passed the secondary school entrance exam were less likely to go to secondary school themselves; with FSE, the effect became positive. A triple differences analysis, using geographic variation in FSE exposure, shows that FSE caused the reversal. Negative pre-FSE spillovers were concentrated in poorer regions. Positive post-FSE spillovers were largest for lower-performing younger siblings. Our results demonstrate that FSE alleviated financial constraints, allowing families to distribute educational investments more equitably rather than concentrating resources on high-performing children.
Keywords: I25; O15; D13; I24; J13; 330; sibling spillovers; free secondary education; intra-household allocation; resource constraints; high-stakes exams; Tanzania